Hybrid Narratives: Exploring Cultural Fusion in The Goats in the Cemetery by Kanogpong Songsompun - Amelia Gustiari; Sulastri Sulastri; Zurmailis Zurmailis (UIN Syarif Hidayatullah Jakarta, 2023)
The short story